Construction and application of textile-based tissue engineering scaffolds: a review. (18th June 2020) - Jiao, Yongjie; Li, Chaojing; Liu, Laijun; Wang, Fujun; Liu, Xingxing; Mao, Jifu; Wang, Lu
Abstract : This review discussed the structure–function relationship of textile-based scaffolds and appropriate textile technologies for application in certain kinds of tissue scaffolds. Abstract : Tissue engineering (TE) provides a practicable method for tissue and organ repair or substitution. As the most important component of TE, a scaffold plays a critical role in providing a growing environment for cell proliferation and functional differentiation as well as good mechanical support. And the restorative effects are greatly dependent upon the nature of the scaffold including the composition, morphology, structure, and mechanical performance. Medical textiles have been widely employed in the clinic for a long time and are being extensively investigated as TE scaffolds. However, unfortunately, the advantages of textile technology cannot be fully exploited in tissue regeneration due to the ignoring of the diversity of fabric structures. Therefore, this review focuses on textile-based scaffolds, emphasizing the significance of the fabric design and the resultant characteristics of cell behavior and extracellular matrix reconstruction. The structure and mechanical behavior of the fabrics constructed by various textile techniques for different tissue repairs are summarized. Furthermore, the prospect of structural design in the TE scaffold preparation was anticipated, including profiled fibers and some unique and complex textile structures. Hopefully, the readers of this review would appreciate the importance of structural design of the scaffold and the usefulness of textile-based TE scaffolds in tissue regeneration.